2019
DOI: 10.31729/jnma.4605
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Substance Use among Undergraduate Students in a Medical College of Nepal

Abstract: Introduction: The consumption of substances is a common practice among the medical students and their use might reduce educational and clinical performances as well as judgment of the students. This study aims to find out the prevalence of substance use among medical students in BP Koirala Institute of Health Sciences. Methods: A descriptive cross-sectional study was carried out among medical students of BP Koirala Institute of Health Sciences from 15th September 15th to December 15th 2018 after obtainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…The results of the study show that the tendency to addiction was different between male and female students; and male students were more likely to abuse drugs, which was consistent with the results of studies of their kind (31)(32)(33)(34)(35), Explaining that entering a new educational environment and having different social and educational expectations from female and male students in the university environment, causes them to experience different issues in the educational environment and therefore There was a difference in the quality of life between the two groups.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results of the study show that the tendency to addiction was different between male and female students; and male students were more likely to abuse drugs, which was consistent with the results of studies of their kind (31)(32)(33)(34)(35), Explaining that entering a new educational environment and having different social and educational expectations from female and male students in the university environment, causes them to experience different issues in the educational environment and therefore There was a difference in the quality of life between the two groups.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, most of the participants were single and there was no relationship between marital status and substance abuse tendency, but domestic research shows that single people are more exposed to substance abuse than married people (29,30). However, some studies show that the rate of substance abuse in married people is higher than single (31).…”
Section: Discussionmentioning
confidence: 56%
“…For example, a previous Bangladeshi study observes similar findings for smoking and gul (powdered tobacco, habitual use is common in South-east Asia) usage (42.2% and 2.2% vs. 2.3% and 1.5%, respectively), although chewing tobacco is higher in female participants (21.6% vs. 19.4%) [31]. Similarly, male participants used more substances than females in Nepal [28] and Ethiopia [30]. Students of arts and commerce backgrounds were reported to have higher substance use behaviors.…”
Section: Plos Onementioning
confidence: 58%
“…The same study also identified that 34.3% of the adolescents reported using any of the substances sometimes during their lifetime [27]. To this end, it can be noted that the diversity of substance use in a particular cohort (medical students, for instance) can vary across the cultures, used methodology, and other factors [28][29][30]. Therefore, cross-cultural studies are needed to provide a better understanding of substance use across countries.…”
Section: Plos Onementioning
confidence: 97%
See 1 more Smart Citation